A CRITICAL REVIEW OF THE ROLE OF FINANCIAL MANAGEMENT IN ENHANCING MACROECONOMIC COMPETITIVENESS: A LITERATURE REVIEW BASED ON ECONOMETRIC AND PUBLIC POLICY APPROACHES - Ummul Chair; Hamka Hamka (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Financial management plays a central role in maintaining economic stability and strengthening macroeconomic competitiveness amid increasingly complex global challenges. This study aims to critically review the relationship between the effectiveness of financial management and the improvement of macroeconomic competitiveness through a literature review based on econometric and public policy approaches. Using a literature review method, this study analyses the empirical results of various previous studies that highlight the relationship between fiscal and monetary policies and public financial management on economic growth and macro stability. The econometric approach is used as a conceptual framework to understand the causal relationship between economic variables, such as government spending, inflation, exchange rates, and GDP, while the public policy perspective is used to assess the institutional dimensions and effectiveness of financial policy implementation. The results of the study show that transparent financial management, fiscal discipline, budget system reform, and cross-sector policy coordination can improve economic efficiency and create sustainable macro stability. In addition, the synergy between fiscal, monetary, and public institutional policies has a significant effect on improving the economic competitiveness index through strengthening innovation, investment, and public confidence in the financial system. This study concludes that financial management based on empirical analysis and adaptive public policy is an important foundation for achieving sustainable macroeconomic competitiveness in the era of globalisation.